The Scope of Adaptability Research to Social, Economic and Policy Changes: The Scope of Adaptability Research to Social, Economic and Policy Changes - Handoko, Jarwa Prasetya Sih; Kusumawanto, Arif; Dharoko, Atyanto (Jurnal Koridor, 2022)
This paper discusses the research on adaptability that has been carried out due to social, economic, and policy changes. The dynamics of social, economic, and policy changes occur along with the development of people's lives. Many factors lead to changes in urban environmental conditions. These dynamics are responded to by the community by making adaptations, both building adaptations and behavioral adaptations. The ability to improve the outcome of existing buildings through adaptation is essential to improving the building environment sustainability. Thus, research on the phenomenon of adaptability is essential and relevant to be carried out, considering that changes in environmental conditions cannot be avoided. Hence, adjustment or adaptation of buildings is necessary. This study's objective is to establish the scope of the research discussion on the topic of adaptability that has been carried out. This research is literature review research with a comparison-content analysis as an empirical method. This study reviews 30 adaptability papers published between 1989 and 2020. The method of analysis is mapping the research literature with the adaptability topic by comparing the substance of the research based on the research focus, objectives, and adaptability research objects carried out. From this research, it can be concluded that research on adaptability can be categorized based on the scope of the research area, the typology of the building being studied, and the research locus. The research results hopefully could provide an extension of other research, specifically in building adaptation.Â It is recommended that further research on the phenomenon of housing adaptation can be carried out with adaptability research in suburban and rural areas. In addition, research can be developed on location settings with different characteristics, such as housing in coastal settlements or settlements in highland settlements.